Optimization of ozone chamber using pulse width modulation for sterilization and preservation on fruits and vegetables - Adi Waskito; Rendra Dwi Firmansyah; Djohar Syamsi; Catur Hilman Adritya Haryo Bhakti Baskoro; Anisya Lisdiana; Herkuswyna Isnaniyah Wahab (National Research and Innovation Agency, 2020)
Ozonizer is a method used for sterilization and food preservation by utilizing ozone produced from plasma discharge. The effective way of obtaining ozone is to use dielectric barrier discharge (DBD) plasma. The manufacture of a controlled ozonizer chamber system is important to result in effective and efficient performance. The aim of this study is to design and optimize the ozone chamber parameter using pulse width modulation (PWM). The system design is added with the Arduino Mega 2560 microcontroller and the L296N motor driver as an ozone generator radiation controller by changing the pulse width modulation to determine the ozone levels produced. The experimental results show that the ozone concentration increases by 50 % on average with increasing variations of the 10 % duty cycle (PWM) and the ignition time length. The optimum value is achieved on a 70 % duty cycle for 60 - 300 seconds, where the ozone level of 3 ppm is obtained and sustained for fruits/vegetables sterilization and preservation application.